Unknown Future of the Banking Union’s Third Pillar - Klaudia Zielińska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the article is to evaluate the process of building the third pillar of the banking union. The analysis of the problem required both subject literature studies and descriptive statistics. Time scope of the analysis covers the years 2012 until 2017. The relevant data used came from the European Central Bank and the European Banking Authority. The results of the study suggest that the creation of a European Deposit Guarantee Scheme is inevitable for further financial integration in the Eurozone but more detailed conditions need to be added to its implementation plan in order to have the scheme established. This stems from both the bad financial standing of some of the euro area banks and their dependency on the sovereign debt of their home and host countries. Studies also indicate low operational readiness of the national schemes, so a transition from re-insurance onto co-insurance phase will require increased efforts of both the Member States and the banks themselves.